(untitled) (Innovative professional education, 2025)
The article is devoted to the consideration of practical psychologists of professional (vocational education) at the present stage. The peculiarities of practical psychologists in wartime involve many professional and personal challenges. Taking into account the peculiarities of professional activity of practical psychologists of institutions of professional (vocational education), knowledge of the causes, levels and consequences of professional deformation of these specialists will ensure its successful prevention. The most effective condition for the organization of prevention of professional deformation is the use of a comprehensive approach